Bioaccessibility of phytoene and phytofluene is superior to other carotenoids from selected fruit and vegetable juices. (15th August 2017) - Mapelli-Brahm, Paula; Corte-Real, Joana; Meléndez-Martínez, Antonio J.; Bohn, Torsten
Highlights: Carotenoid bioaccessibility (BA) was assessed in 4 vegetable and fruit juices. The BA of the major dietary carotenoids and that of phytoene/phytofluene was compared. Phytoene had the highest BA, followed by phytofluene in almost all juices. The markedly different shape of phytoene/phytofluene could explain their high BA. The BA of phytoene varied between 32 and 97%, that of phytofluene between 27 and 94%. Abstract: Phytoene and phytofluene are major abundant dietary carotenoids largely ignored in the context of agro-food and health. The bioaccessibility of phytoene and phytofluene in tomato, carrot, blood orange (sanguinello cultivar), and apricot juices was analysed following simulated gastro-intestinal digestion with coffee cream as a lipid source, and compared with that of other main carotenoids from these matrices. The bioaccessibility of phytoene and phytofluene, and also total carotenoid bioaccessibility, followed the order: sanguinello > apricot > tomato > carrot. Phytoene was consistently the carotenoid with the highest bioaccessibility, up to 97%, generally followed by phytofluene. The higher bioaccessibility of these carotenoids could mainly be due to their marked difference in chemical structure and matrix distribution. For most juices, cis- isomers presented a higher bioaccessibility than their all- trans counterparts ( P  < 0.05). The dietary source that provided highest amounts of potentially absorbable phytoene/phytofluene was by far tomato juice (5 mg/250 mL juice).